Location Analysis for Retail Property Investment– A GIS Based Approach: Case Study of Blantyre City - Namangale, Desmond; Dunga, Grace (Journal of Techno-Social, 2022)
Although there is an increased retail property investment interest, location analysis for retail outlets is inadequate. Site selection is the most significant process in retail property investment decision making. Due to its complexity, location determination can contribute to the success or failure of real estate investment. Optimal location is relevant in a competitive market as it contributes to guaranteed increased returns. Real estate investors can evaluate a set of potential sites for locating a new retail outlet. This study aimed at analyzing how GIS can contribute to the success of retail property investment positioning through spatial data analysis. The study used GIS application to find optimal location for retail property investment in Blantyre City, Malawi. The criteria for finding suitable sites were demographics, transportation and competiveness. The findings presented the applicability, efficiency and productivity of using GIS in location analysis. Based on the findings GIS can help in identifying optimal location through maximizing retail store patronage thereby increasing retail investment return.